The use of chatbots as interventions for mental health conditions: scoping review of systematic reviews and meta-analyses - Khanh Dang Bao Tieu; Felix Agyapong-Opoku; Belinda Agyapong (Frontiers in Digital Health, 2026)
Background During the COVID-19 pandemic, the use of mental health chatbots received potential attention as a means of addressing the increase in demand for mental healthcare, which has become inaccessible due to a shortage of healthcare workers and lockdown. Even after the pandemic, chatbot versatility holds the potential to address the ongoing limited accessibility of mental healthcare due to a shortage of professionals, geographical challenges, cost, or stigma. Objective This review examines the scope and nature of the systematic review and meta-analysis evidence on chatbot interventions for mental health. Method This scoping review follows Arksey and O'Malley's five-step guide and was reported using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for scoping reviews (PRISMA-ScR). The following databases were used to conduct all systematic literature searches: PubMed, Scopus, Medline, and Web of Science. Inclusion criteria include systematic reviews and meta-analyses, written in English, that focus on the use of chatbots as an intervention for mental conditions, with all primary articles being relevant. A total of 14 articles were relevant and included in the data extraction and analysis. Results It was found that although current review-level evidence suggests potential short-term benefits, there was a discrepancy regarding the specific conditions under which chatbots are effective. Moreover, the use of chatbots for symptom improvement is still inconclusive, since there are issues with important aspects such as unclear risk of bias, lack of longitudinal studies, and lack of comparison with traditional therapy. Conclusion There is potential for chatbot implementation as an intervention for mental conditions. However, this is still at its early stages of development and requires more research to improve communication quality and ensure safety, which is paramount when communicating with vulnerable patients. The findings of the review provide a useful foundation for informing clinical practice, policy, and future research.